The second and third levels of digital divide among Malaysian university students during the Covid-19 pandemic - Latha Subramaniam; Farah Waheeda Jalaludin; Kai Wah Hen; Ching Seng Yap (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Adaptation of online learning among Malaysian universities during the Covid-19 pandemic stressed the dire need to tackle digital divide. Lack of empirical evidence, generic highlights on accessibility to technologies and lack of focus given on gaps in skills, usage and outcomes obscures the extent of digital divide among Malaysian students. Data was collected from 356 undergraduate students of private and public universities to identify the differences in second and third levels of digital divide, where the former entails divide in terms of digital skills and digital usage, then the latter concerns online learning outcomes between students from both types of Malaysian universities. Descriptive results unveiled the persistence of digital divide in the second and the third level among both public and private university students, with exception of students from public universities showing an advanced grasp of digital skills. Path analysis have also highlighted that having digital skills would encourage digital usage. Although digital usage equips students with resources and support for their learning attainment, at the same it also creates digital distraction, which diverts students from acquiring online learning fulfilment.